Degradation of low-density polyethylene using bacillus subtills - Anis Syakirah, Ahmad Murtadza (2025)
Low-Density Polyethylene (LDPE), widely used for its durability and flexibility, poses significant environmental challenges due to its non-biodegradable nature. Current methods to manage LDPE waste, such as recycling and incineration, remain inefficient and environmentally detrimental. This study investigates the potential of Bacillus subtilis to biodegrade LDPE through an innovative, sustainable approach. Over a 30-day incubation period, LDPE films were exposed to Bacillus subtilis in controlled conditions. The study evaluated degradation using weight loss measurements, microscopic analysis, ATR-FTIR spectroscopy, and SDS-PAGE for enzyme identification. Results demonstrated notable weight loss in LDPE films and surface morphological changes, including cracks and pits, suggesting microbial enzymatic activity. ATR-FTIR analysis confirmed chemical modifications in the polymer, with emerging functional groups indicative of oxidation and polymer backbone breakdown. SDS-PAGE further identified key enzymes potentially responsible for LDPE degradation. These findings highlight the promising role of Bacillus subtilis in addressing plastic pollution and underscore the importance of optimizing microbial-based degradation systems for scalable environmental applications.